THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN AN ESP CLASS TO IMPROVE READING AND SPEAKING SKILLS - Ignatius Indra Kristianto; Monica Ella Harendita (ELTR Journal, 2022)
Employing a descriptive qualitative method, the study aims at describing how the implementation of Project-Based Learning (PBL) has improved students’ reading and speaking skills in an English for Specific Purposes (ESP) class at Universitas Atma Jaya Yogyakarta. The contextual and real-life situations designed in PBL are expected to equip them better to practice the language and apply the content knowledge. The results of the questionnaires and interviews suggest that the students generally perceived PBL as an effective and creative method in learning. It has also helped them acquire better reading and speaking skills through the accomplishment of a variety of group projects. The improvements cover, among others, vocabulary, grammar as well as fluency and confidence in speaking. It is hoped that this research can provide benefits to researchers and FBE UAJY in general. The results of this study may provide meaningful inputs on the process of teaching and learning activities. Thus, ESP lecturers can find the most appropriate method to improve students’ English skills.